Treatment of peri-invagination lesion and vitality preservation in an immature type III dens invaginatus: a case report - Ju-Kyung Lee; Jae Joon Hwang; Hyeon-Cheol Kim (BMC, 2020)
Abstract Background To report a case of type III dens invaginatus associated with peri-invagination periodontitis in an immature permanent mandibular central incisor with open apex, in which only the invagination area was treated and vitality was preserved. Case presentation A 9-year-old boy was referred complaining of pain in the mandibular left central incisor. After radiographic examination, an invagination into the pulp chamber of the tooth associated with periapical radiolucency was detected. Endodontic access was performed and the orifice was identified under a dental operating microscope. The invagination area was chemo-mechanically cleaned. After 1 week, the invagination was obturated with mineral trioxide aggregate. During the 2-year follow up period, the tooth was asymptomatic. Radiographic examination revealed significant progression of periapical healing and root development in the main root canal of the tooth. Conclusion Non-surgical root canal treatment of the invagination may preserve pulp vitality, and continuous root development of the tooth.